Understanding the Key to Targeting the IGF Axis in Cancer: A Biomarker Assessment - Lodhia, Kunal Amratlal; Tienchaiananda, Piyawan; Haluska, Paul (Frontiers in Oncology, 2015)
Type 1 insulin like growth factor receptor (IGF-1R) targeted therapies showed compelling pre-clinical evidence; however, to date, this failed to translate to patient benefit in Phase 2/3 trails in unselected patients. This was further complicated by the toxicity, including hyperglycemia, which largely results from the overlap between IGF and insulin signaling systems and associated feedback mechanisms. This has halted the clinical development of inhibitors targeting IGF signaling, which has limited the availability of biopsy samples for correlative studies to understand biomarkers of response. Indeed, a major factor contributing to lack of clinical benefit of IGF targeting agents has been difficulty in identifying patients with tumors driven by IGF signaling due the lack of predictive biomarkers. In this review we will describe the IGF system, rationale for targeting IGF signaling, the potential liabilities of targeting strategies and potential biomarkers that may improve success.